G164 Nurture early for optimal nutrition (neon) programme: qualitative study of drivers of infant feeding practices in a british-bangladeshi population. (25th October 2020) - Benton, L; Lloyd, O; Heys, M; Manikam, L; Lakhanpaul, M
Abstract : Aims: To explore optimal nutritional care practices and their drivers within the British Bangladeshi population as an exemplar to inform a tailored, co-adapted intervention design. Methods: Qualitative community based participatory research. Multiple recruitment strategies were used to purposively sample the British Bangladeshi population. Community facilitators were an active partner in this study and worked as a bridge to the community. A total of 145 participants completed the study and were recruited to 12 focus groups and 45 semi-structured interviews, including; British Bangladeshi mothers, fathers, grandmothers and grandfathers of infants and young children aged 6–23 months; key informants and lay community members from the British Bangladeshi population and health professionals. Transcripts were then checked and were analysed using framework analysis. Results: Two overarching themes were identified during interviews and group discussions: (1) modifiable infant feeding practices that participants suggested could be targeted in order to optimise infant feeding and (2) socio-ecological factors believed by participants to influence these modifiable feeding practices. Participants discussed several infant feeding practices that may restrict dietary diversity, override infant satiety and encourage dependence on sugary or sweetened foods and impact on broader care practices such as sleeping and physical activity. Specifically, four modifiable infant feeding and care practices were highlighted: untimely introduction of semi- and solid foods, overfeeding, prolonged parent-led feeding and feeding to 'fill the belly'. These practices were driven by factors at all socio-ecological levels, categorised as: society, culture and religion, physical and local environment and information and awareness. Conclusions: Parenting interventions need to be culturally sensitive to populations of diverse ethnicity and recognise the social and cultural norms that inform complementary feeding practices. Further, the infant feeding environment requires better regulation of marketing of foods for infant and young children. More evidence is needed to inform effective early years interventions.